CEMENT ADDITIVE USE REDUCTION FACTORS TO IMPROVING THE QUALITY CONCRETE BIOCONC - Muhammad chabibullah; Tony Hartono Bagio (NAROTAMA UNIVERSITY, Indonesia)
Technology applications in the concrete mix is ??growing very rapidly in this modern era to obtain concrete results with characteristics that are environmentally friendly and non-toxic. Bioconc is innovation in developing green technology with the insertion of a micro-gap or slit gradation mycelia microbe as a micro-filter to mengoptimalkanatau reduce the amount of cement concrete on the concrete mix in total will increase the efficiency in the concrete and reduce the material components of the most expensive in the concrete, the cement. in job mix additive Bioconc require R%, ie a reduction factor of cement that will determine how the dose of cement and dose additive Bioconc, and therefore to seek R% require some percentage of reduction factor of cement optimum ranging from the concrete Normal, 5%, 10%, 15%, 20%, 25%, 30%, 35%.? + 31271x? - 4709x³ - 233.1x² + 79.66x + 22:18, concrete quality obtained from normal concrete with fc '= 20 MPa generate optimum value reduction of cement amounted to 28.869%.